Complex variables and applications - Brown, James Ward 1899-1987; Churchill, Ruel V. (Brown and Churchill series, 2014)
Suitable for an introductory course in the theory and application of functions of a complex variable, this title is designed to develop the theory that is prominent in applications of the subject. It helps you find a special emphasis given to the application of residues and conformal mappings.